(untitled) (Colombia Medica, 2025)
Introduction It is suggested that chronic obstructive pulmonary disease (COPD) patients have high death anxiety and the majority of them tend to search for COPD-related information on the internet. Objective Explore the association between death anxiety and cyberchondria in patients with COPD Methods This descriptive, cross-sectional study included 143 patients diagnosed with COPD aged 45 years or older, who had no sensory impairments affecting communication, were cognitively intact, and actively used the internet Results A multiple regression analysis examining the Cyberchondria Scale (CS-12) total score in relation to sociodemographic and clinical characteristics found that marital status, regular use of medications, having a COPD exacerbation in the last 6 months, and daily internet use time together explained 35.8% of the variance in the Cyberchondria Scale (CS) score (Adj R2= 0.358, p <0.001). Additionally, it was discovered that doing regular breathing exercises, being hospitalized in the last 6 months, searching for information about the COPD on the internet and use any medication other than those prescribed (such as analgesic, antipyretics, anti-emetics, etc.) by their doctor in the last year explained 37.3% of the variance in the Death Anxiety Score (Adj R2= 0.373, p <0.001) Conclusion The findings indicate that patients with COPD exhibited moderate levels of cyberchondria and high levels of death anxiety, highlighting the relevance of psychological factors in this patient group.